Tree health influences diameter growth along site quality, crown class and age gradients in Nothofagus forests of southern Patagonia - Attis Beltran, Hernan (2013)
We examined the influence of tree health on annual diameter increment of trees along gradients in stand site quality, crown classes and tree age in Nothofagus pumilio forests of Southern Patagonia. Healthy trees had higher annual diameter increment than unhealthy trees along all gradients (site quality, crown class, tree age). We argue that tree health could be employed as a qualitative variable in models of tree growth to estimate aboveground biomass and carbon stocks in this forest system.